Methylomic Aging as a Window onto the Influence of Lifestyle: Tobacco and Alcohol Use Alter the Rate of Biological Aging. Issue 12 (14th November 2015) - Beach, Steven R. H.; Dogan, Meeshanthini V.; Lei, Man‐Kit; Cutrona, Carolyn E.; Gerrard, Meg; Gibbons, Frederick X.; Simons, Ronald L.; Brody, Gene H.; Philibert, Robert A.
Abstract : Objectives: To examine the effect of the relationship between alcohol and cigarette consumption on biological aging using deoxyribonucleic acid methylation‐based indices. Design: Hierarchical linear regression modeling followed by fitting of higher‐order effects. Setting: Longitudinal studies of aging and the effect of psychosocial stress. Participants: Participants in two ethnically informative cohorts (n = 656 white, n = 180 black). Measurements: Deviation of biological age from chronological age as a result of smoking and alcohol consumption. Results: Greater cigarette consumption was associated with accelerated biological aging, with strong effects evident at even low levels of exposure. In contrast, alcohol consumption was associated with a mixed effect on biological aging and pronounced nonlinear effects. At low and heavy levels of alcohol consumption, there was accelerated biological aging, whereas at intermediate levels of consumption there was a relative decelerating effect. The decelerating effects of alcohol were particularly notable at loci for which methylation increased with age. Conclusion: These data support prior epidemiological studies indicating that moderate alcohol use is associated with healthy aging, but we urge caution in interpreting these results. Conversely, smoking has strong negative effects at all levels of consumption. These results also support the use of methylomic indices as a tool for assessing the impact of lifestyle on aging.